Bacterial Exchange in Household Washing Machines - Callewaert, Chris; Van Nevel, Sam; Kerckhof, Frederiek-Maarten; Granitsiotis, Michael S.; Boon, Nico (Frontiers in Microbiology, 2015)
Household washing machines launder soiled clothes and textiles, but do not sterilize them. We investigated the microbial exchange occurring in five household washing machines. Samples from a new cotton T-shirt were laundered together with a normal laundry load. Analyses were performed on the influent water and the ingoing cotton samples, as well as the greywater and the washed cotton samples. The number of living bacteria was generally not lower in the washing machine effluent water as compared to the influent water. The laundering process caused a microbial exchange of influent water bacteria, skin- and clothes-related bacteria and biofilm-related bacteria in the washing machine. A variety of biofilm-producing bacteria were enriched in the effluent after laundering, although their presence in the cotton sample was low. Nearly all bacterial genera detected on the initial cotton sample were still present in the washed cotton samples. A selection for typical skin- and clothes-related microbial species occurred in the cotton samples after laundering. Accordingly, malodour-causing microbial species might be further distributed to other clothes. The bacteria on the ingoing textiles contributed for a large part to the microbiome found in the textiles after laundering.